DISKURSUS STUDI HADIS DALAM WACANA ISLAM KONTEMPORER - Nirwana, Dzikri (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2014)
In the Islamic discourse, the study of hadith is in demand today. This is because the function of hadith is as a source of Islamic teachings which is a necessity in human life in all circumstances and conditions. Therefore, the proper method of understanding hadith through comprehensive approach both textual and contextual is required. The study of hadith also needs methodology enlightenment and paradigm shift. In this case, modification and adaptation of information and methodology elements by a discipline from other disciplines is a natural thing. This integration of various diciplines is then known as interdisciplinary and multidisciplinary approach. Interdisciplinary approach in the study of hadith which use the traditional Islamic science is also done by a number of contemporary scholars of hadith